O papel da distância em projetos topológicos de redes de distribuição elétrica - Silva, Paulo Wagner Lopes da (2015)
This dissertation investigates in which conditions the optimal configuration of an electric power network is a minimum length spanning tree, and in which conditions it is shortest path tree configuration. For this purpose the dissertation, it applies computational optimization mathematical models of an optimal local access network design problem. The focus of the study is the 13.8 kV spacer cable primary radial networks. Applied models seek for the balance between fixed costs and variable costs. Saved values from an optimal network could be applied to increase the range of the network and people reached as well. The bibliographic research is compound by three parts: graph theory, local access network optimization models, and distribution network costs. Research methodology includes the choice of the distribution system, determination of fixed and variable costs, choice and implementation of the local access network optimization models, tests in hypothetical and realistic systems by using the CPLEX solver, analysis of the resulting configuration, and construction of graphics to facilitate the results evaluation. It was found that the relationship between fixed costs and variable costs inï¬‚uences the optimal configuration of the distribution network in such a way that a low value of the quotient between fixed costs and variable costs contributes to a shortest path tree. On the other hand, a high quotient between fixed costs and variable costs contributes to a minimum length spanning tree confïguration. However, others parameters must be considered to determine the network confïguration such as extension, arches demand and quantity of arches.